Acid-base bifunctional catalyst with coordinatively unsaturated cobalt-nitrogen sites for the simultaneous conversion of microalgal triglycerides and free fatty acids into biodiesel. (April 2022) - Guo, Hao; Cheng, Jun; Mao, Yuxiang; Qian, Lei; Shao, Yang; Yang, Xiao; Yang, Weijuan
Highlights: Novel bifunctional heterogeneous catalyst was synthesized for biodiesel production. The breakage of Co-N bands in ZIF-67 enhanced Lewis acid-base properties of catalyst. DFT calculation reveled destruction mechanism of Co-N4 and reaction pathway of lipids. The conversion efficiency of microalgal lipids to FAME with ZC-450 was 96.7% Abstract: An acid-base bifunctional catacknalyst with coordinatively unsaturated cobalt-nitrogen active sites Co-Nx (x < 4) was synthesized to convert microalgal lipids with high acid value into biodiesel. Pyrolysis destroyed Co-N4 coordination structure in ZIF-67 and released coordinatively unsaturated Co-Nx and uncoordinated N sites, which resulted in the Lewis/Brønsted acid ratio increasing from 0.1 to 11.45 and the basicity increasing from 0.96 to 6.05 mmol/g. According to DFT calculations, the adsorption energy of free fatty acid (FFA) on Co-N2 site (-1.003 eV) exceeded that on Co-N4 site (-0.271 eV). The strong interaction between Co-N2 site and FFA increased electropositivity of carbonyl carbon atom in FFA from 1.379 to 1.529 eV and promoted esterification. The pyrolysis-induced defects generated more mesopores to promote the transportation of lipid molecules inside the catalyst. Therefore, the conversion efficiency of microalgal lipids into biodiesel over the ZC-450 catalyst (96.7%) was higher than that over the ZIF-67 catalyst (69.5%).